ANALISIS PENGARUH PERUBAHAN BEBAN TERHADAP KONSUMSI BATUBARA, HEAT RATE DAN EFISIENSI TERMAL PLTU INDOEKA UNIT 1 - Alfarisi, Dafid Imam; Rumawan, Fatkhul Hani; Wirawan, Adi Pandu (Universitas Mulawarman, 2024)
With the availability of energy needs every year, the government on the other hand must also reduce exhaust emissions to reduce the greenhouse effect. One way to reduce exhaust emissions is by energy efficiency. Because steam power plants use burning coal to heat air into dry steam, fuel consumption, heat rate and thermal efficiency will influence changes in the load of steam power plants. Before researchers carry out calculations to find SFC values, plant heat rate and thermal efficiency, researchers must select data from the database. The selection of this data refers to the lowest generation load and the following data increases the load by 10 MW from the previous data, until the maximum load is obtained in multiples of 10 MW. Obtained load values of 40 MW, 50 MW, 60 MW, 70 MW, 80 MW and 90 MW from data selection. As the electricity loading value increases, the Net SFC value tends to get lower. This shows that under high electricity loading conditions, the amount of coal consumed per kWh is less than under low electricity loading conditions. As the electrical loading value increases, the NPHR value will become lower. This shows that at high loads, the noise from a generating unit will also be higher. On the other hand, at low loads, the noise from a generating unit will also decrease. As the electrical loading value increases, the thermal efficiency value of the Indoeka Unit 1 Steam Power Plant also increases and can be said to be efficient. This shows that under high load conditions, the percentage between the energy produced and the energy consumed is also higher.